A Functional Beverage from Coffee and Olive Pomace: Polyphenol-Flavonoid Content, Antioxidant, Antihyperglycemic Properties, and Mouse Behavior - Analy Aispuro-Pérez; Fernando Javier Pedraza-Leyva; Alicia Ochoa-Acosta; Mayra Arias-Gastélum; Feliznando Isidro Cárdenas-Torres; Bianca Anabel Amezquita-López; Emiliano Terán; Emmanuel Aispuro-Hernández; Miguel Ángel Martínez-Téllez; Roberto J. Avena-Bustillos; Selina C. Wang; Eli Terán-Cabanillas; et al. (Foods)
Background: Coffee is widely consumed worldwide and is rich in polyphenols with antioxidant properties linked to a reduced risk of metabolic and cardiovascular diseases. Olive pomace (OP), a by-product of olive oil production, contains phenolic compounds with cardioprotective effects but is often discarded. Combining it with coffee could enhance health benefits and promote sustainability. Methods: Soluble solids, total phenols, flavonoids, and antioxidant capacity (DPPH• scavenging activity) were analyzed in C-OP at 5%, 10%, 15%, and 20% OP concentrations. The C-OP 10% brew was selected for further evaluation with α-amylase inhibition and a 14-day pilot study in a murine model, evaluating weight, food and liquid intake, and behavior, compared to a control group. Results: Adding OP powder to ground coffee increased the total phenol content in the brews. The highest antioxidant activity (6.62–8.17 mmol TE/L) was found in those brewed from 10%, 15%, and 20% concentrations. The C-OP 10% brew had the highest acceptance in mice, with increased consumption, greater exploratory behavior, and reduced resting time. It also showed 30.5% α-amylase inhibition at 200 µg/mL. Conclusions: The incorporation of OP into coffee enhances its total phenol content and antioxidant capacity. The C-OP 10% brew showed optimal bioactivity, suggesting its potential as a functional beverage for metabolic health.